Transformation of Family Roles and Dynamics In Adjusting to the Industrial Revolution 4.0 for Prosperity in Digital Era - Jum Anggriani; Maimun; Indah Harlina; Suhendar (International Journal of Educational Research Excellence (IJERE), 2024)
The fourth industrial revolution has brought about major changes in how we live and labor, specifically affecting family dynamics. This abstract explores how families adjust to these changes to maintain productivity and well-being in the digital age. We concentrate on the effects of technology adoption on the labor market and the necessary skills, including automation, artificial intelligence, and the Internet of Things (IoT). Adapting abilities to stay professionally relevant and maintain social-emotional balance in the face of evolving digitally affected interaction patterns is a major problem for families. This study emphasizes how crucial it is for families to adjust quickly in order to acquire new skills and maintain up good communication. We demonstrate how families can prosper in the digital age by effectively adapting. Families that recognize and solve these issues will be able to maintain their well-being in the face of swift global change.